Effects of osteoblast-derived extracellular vesicles on aggressiveness, redox status and mitochondrial bioenergetics of MNNG/HOS osteosarcoma cells - Ponzetti, Marco; Ucci, Argia; Puri, Chiara; Giacchi, Luca; Flati, Irene; Capece, Daria; Zazzeroni, Francesca; Cappariello, Alfredo; Rucci, Nadia; Falone, Stefano (Frontiers in Oncology, 2022)
Osteosarcoma is the most common primary bone malignancy. The crosstalk between osteosarcoma and the surrounding tumour microenvironment (TME) drives key events that lead to metastasization, one of the main obstacles for definitive cure of most malignancies. Extracellular vesicles (EVs), lipid bilayer nanoparticles used by cells for intercellular communication, are emerging as critical biological mediators that permit the interplay between neoplasms and the tumour microenvironment, modulating re-wiring of energy metabolism and redox homeostatic processes. We previously showed that EVs derived from the human osteosarcoma cells influence bone cells, including osteoblasts. We here investigated whether the opposite could also be true, studying how osteoblast-derived EVs (OB-EVs) could alter tumour phenotype, mitochondrial energy metabolism, redox status and oxidative damage in MNNG/HOS osteosarcoma cells.These were treated with EVs obtained from mouse primary osteoblasts, and the following endpoints were investigated: i) cell viability and proliferation; ii) apoptosis; iii) migration and invasive capacity; iv) stemness features; v) mitochondrial function and energy metabolism; vi) redox status, antioxidant capacity and oxidative molecular damage. OB-EVs decreased MNNG/HOS metabolic activity and viability, which however was not accompanied by impaired proliferation nor by increased apoptosis, with respect to control. In addition, OB-EV-treated cells exhibited a significant reduction of motility and in vitro invasion as compared to untreated cells. Although the antioxidant N-acetyl-L-cysteine reverted the cytotoxic effect of OB-EVs, no evidence of oxidative stress was observed in treated cells. However, the redox balance of glutathione was significantly shifted towards a pro-oxidant state, even though the major antioxidant enzymatic protection did not respond to the pro-oxidant challenge. We did not find strong evidence of mitochondrial involvement or major energy metabolic switches induced by OB-EVs, but a trend of reduction in seahorse assay basal respiration was observed, suggesting that OB-EVs could represent a mild metabolic challenge for osteosarcoma cells. In summary, our findings suggested that OB-EVs could serve as important means through which TME and osteosarcoma core cross-communicate. For the first time, we proved that OB-EVs reduced osteosarcoma cells’ aggressiveness and viability through redox-dependent signalling pathways, even though mitochondrial dynamics and energy metabolism did not appear as processes critically needed to respond to OB-EVs.